THE EDUCATIONAL MANAGEMENT OF PASRAMAN SHANTI YADNYA IN STRENGTHENING THE CHARACTER OF THE YOUNG HINDU GENERATION - Oktaviani, Putu Nova; Sudarsana, I Ketut (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The research aimed to analyze the educational management of Pasraman Shanti Yadnya in strengthening the character of the young Hindu generation. The government seeks to enhance character on various educational pathways. Educational pathways are divided into three; informal, formal, and non-formal. Pasraman, as one of the non-formal educational pathways, also has a noble goal to achieve better education for the young generation. This type of research was qualitative research with the phenomenological approach. The data collection method used was observation, interviews, and document studies. The results showed that the management carried out by Pasraman Shanti Yadnya, namely: a) content standard management, b) process standard management, c) graduate competency standard management, d) Management of educators and education personnel, e) facilities and infrastructure management, f) Management of management, g) financing standard management, h) Management of assessment standards education.